Conserved guanine-guanine stacking in tetraplex and duplex DNA - Kypr, J; Fialová, M; Chládková, J; Tůmová, M; Vorlícková, M (European biophysics journal, 2001)
Using a series of suitably chosen oligonucleotides, we demonstrate that the DNA duplex of d(CCCCGGGG) provides an almost identical CD spectrum as the parallel-stranded tetraplex of d(GGGG). The CD spectra are very sensitive to base stacking in DNA so that the above observation indicates that guanine-guanine stacking is essentially the same within the duplex of d(CCCCGGGG) and the tetraplex of d(GGGG). A very similar CD spectrum is also provided by the A-form of d(CCCCGGGG) induced by trifluoroethanol. These results reveal that guanine-guanine stacking is a structural invariant conserved in various nucleic acid conformers. The structural invariance is likely to cohere with evolution of the genetic molecules and be important for fundamental functions, e.g. initiation of transcription.
Keywords: genetická transkripce; Nucleic Acids; Circular Dichroism; Electrophoresis, Polyacrylamide Gel; Guanine; Transcription, Genetic; DNA; cirkulární dichroismus; Protein Conformation; Nucleic Acid Conformation; polytetrafluoroethylen; nukleové kyseliny; guanin; elektroforéza v polyakrylamidovém gelu; Polytetrafluoroethylene; konformace nukleové kyseliny; konformace proteinů